2017
DOI: 10.1039/c6nr08706j
|View full text |Cite
|
Sign up to set email alerts
|

Tunable superapolar Lotus-to-Rose hierarchical nanosurfaces via vertical carbon nanotubes driven electrohydrodynamic lithography

Abstract: The development of an advanced technique that enables fabrication of superhydrophobic structured surfaces, easily tuneable from lotus-leaf to rose-petal state is essential to realise the full applied potential of such architectures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…In 2000, Schaffer et al reported a straightforward, cost-effective and contactless (positive replica) patterning technique, electrohydrodynamic patterning (EHDP), that creates and replicates lateral hierarchical structures with a submicrometre length scale on various kinds of materials ( e.g. thermoplastic polymer, 15–22 thermosetting polymer, 23–29 photocurable resin, 30–34 ceramic, 35–37 and so on) under an externally applied electric field. 38–47 Especially, the capability of EHDP with a featureless template to fast and economically create large-scale three-dimensional micro-scale structures, even though no long range order, is particularly attractive because the difficulty, time, and cost in designing and making pre-patterned templates limit the flexibility and wide application of conventional lithography, especially when large numbers of different patterns are to be fabricated.…”
Section: Origin Of Ehdpmentioning
confidence: 99%
“…In 2000, Schaffer et al reported a straightforward, cost-effective and contactless (positive replica) patterning technique, electrohydrodynamic patterning (EHDP), that creates and replicates lateral hierarchical structures with a submicrometre length scale on various kinds of materials ( e.g. thermoplastic polymer, 15–22 thermosetting polymer, 23–29 photocurable resin, 30–34 ceramic, 35–37 and so on) under an externally applied electric field. 38–47 Especially, the capability of EHDP with a featureless template to fast and economically create large-scale three-dimensional micro-scale structures, even though no long range order, is particularly attractive because the difficulty, time, and cost in designing and making pre-patterned templates limit the flexibility and wide application of conventional lithography, especially when large numbers of different patterns are to be fabricated.…”
Section: Origin Of Ehdpmentioning
confidence: 99%
“…[5][6][7][8][9][10] Among the surface structures, nanotubes were reported as unique surface structures with tunable surface hydrophobicity and water/substrate adhesion. [10][11][12][13][14][15][16] To find a relationship between the nanotube dimensions (diameter, height, porosity, shape) and the surface wetting properties it is fundamental to well control the surface structures. The achievement of ordered nanotubes on substrate often needs multi steps with the use of hard templates, typically porous membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting to ordinary superwettability membranes, lotus leaf's upper and lower surfaces possess self‐cleaning performance and strong stability on the air‐water interface, respectively. [ 23–25 ] B. splendens 's body and fins exhibit the additional capability to change its color by control inside periodic guanine platelet arrays. [ 26–28 ] In order to mimic this characteristic, intelligent structural color hydrogels, constructed by imparting the intelligent responsive polymers with periodical nanostructures that could modulate light propagation, have been developed.…”
Section: Introductionmentioning
confidence: 99%